PO.7.151 The relationship between health-related quality of life and disease activity in sle patients. (27th September 2022) - Salvucci, S; Santangeli, R; Montozzi, G; Gamba, L; Cocco, C; Fioretti, P; Manfredi, L; Moroncini, G
Abstract : Purpose: Systemic lupus erythematosus (SLE) treatment has two objectives: disease activity control and damage progression prevention. These clinical aspects should be regularly measured by validated scores. Unfortunately, these instruments do not take into account the health-related quality of life (HRQoL), often compromised in SLE patients, even among those with mild or inactive disease. This preliminary study examines the relationship between disease activity scores and HRQoL changes in SLE patients and will then be followed by another study to evaluate whether a multidisciplinary approach (based on yoga, mindfulness and Chinese medicine), in addition to conventional medical therapy, could improve quality of life. Methods: This is a cross-sectional observational study of SLE patients in a tertiary disease-specific outpatient clinic. During clinical evaluation, for each enrolled patient, demographics, drugs, organ damage (Systemic Lupus International Collaborating Clinics Damage Index), active disease manifestations, and Systemic Lupus Disease Activity Index scores are recorded. At the same time, patients complete two questionnaires, the Short Form-36 (SF-36) and the Functional Assessment Chronic Illness Therapy-Fatigue (FACIT-F), considered as patient reported outcome scores (PRO scores). Results: Although the study is still ongoing, we are presenting preliminary data. 17 outpatients have been enrolled since January 2022 (mean age 41.7±16.4 years, median duration of the disease 7.5 years). The median scores of SLEDAI-2K, SLICC-DI, SLEDAs, FACIT-F, and SF-36 (physical and mental component) are, respectively, 2 (IQR 0.5–4), 0 (IQR 0–0), 1.12 (IQR 0.28–6.88), 38.5 (28.75–46.25), 43 (IQR 36.5–51), 36 (IQR 19–50). Of the patients in our cohort, 10/17 (58.8%) met the definition of Lupus Law Disease Activity State (LLDAS), while 4/17 (23.5%) manifested an active disease. In preliminary data analysis, there is no evidence of correlation between lower disease activity and better PRO score. The study is expected to be completed in May 2022 and the final data will be available from June 2022. Conclusions: While research has recently begun, there seems to be a discordance between physician's and patient's disease perception. SLE patients often feel misunderstood and complain that doctors do not take care of all aspects of the disease. We are sure that the multidisciplinary approach proposed at the end of the study will overcome this gap in healthcare.